EVALUASI PELAKSANAAN KEWENANGAN DESA DI BIDANG KESEHATAN DI DESA BATURIJAL BARAT KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Patimah, Siti; Munaf, Yusri (UIR PRESS, 2016)
This study berujuan to see the implementation of the Authority of the Village Health Sector paired with District Regulation Indragiri Hulu No. 4 of 2008 on the Authority of the Village in particular Article 3 g, and the Regulation of the Minister of Home Affairs Number 54 Year 2007 on Guidelines for the Establishment of the Working Group Operational Development of Postal Services integrated. With ditertibkannya a policy that can be expected to ease in running the village authorities. Indicators in this study is, Effectiveness, Efficiency, and Precision. This research is a quantitative research which refers to the formulation of the problem that the data and information obtained and collected from various surveys which serve as the basis for describing and describing the research. The data collection is done with the survey in addition also be obtained by conducting interviews To the Village Head, Chairman of the Village Consultative Body, and Kader Integrated Service Post. With data collection by observation and direct interaction associated Implementation Authority is expected to vote on the Rural Health Sector contains data that is Real and contains a truth value to the regional Regulation provides benefits and use value. That based on the results of research that has been done, the conclusions of researchers on the Evaluation of the Village Authority in the Health Sector in the village of West Baturijal Peranap District of Indragiri Hulu is